Hexavalent chromium removal in a tannery industry wastewater using rice husk silica - D. Sivakumar (Global Journal of Environmental Science and Management)
Present study dealt the removal of Cr(VI) in a tannery industry wastewater using rice husk silica powder as an adsorbent.The experimental investigations have been carried out by using rice husk silica powder for different adsorption dosage, different contact time and different pH against the initial Cr(VI) concentration of 292 mg/L. The maximum percentage removal of Cr(VI) in the tannery industrial wastewater (88.3 %) was found at an optimum adsorbent dosage of 15 g, contact time of 150 min., and pH of 4.  Further, the experimental data on removal of Cr(VI) from tannery industry wastewater was validated with the Cr(VI) aqueous solution of same initial concentration of tannery industry waster against the optimum process parameters. The results of the validation experiment showed that the experiments conducted for the removal of Cr(VI) in a tannery industry wastewater may be reproducing capability for analyzing various parameters along with Cr(VI) based water and industry wastewater.  The experimental data were fitted to Langmuir and Freundlich isotherm models.  Isotherm models result indicated that the equilibrium data fitted well with the Langmuir isotherm than Freundlich isotherm, because of higher correlation created between dependent and independent variables. Thus, the adsorption method using rice husk silica powder was used effectively for removing Cr(VI) in the tannery industrial wastewater, seems to be an economical and worthwhile alternative over other conventional methods, because of their abundant source, low price, multi-purposes and antimicrobial properties.